KETIDAKADILAN DPR-RI DALAM MENJALANKAN FUNGSINYA - Sulistyowati, Sulistyowati (Faculty of Social and Political Sciences Diponegoro University, 2011)
Abstract :DPR (house of representative)has three main duty; legislation, budgeting and supervision. However the result have not significantly satisfied citizen, particularlythe function of budgeting and legislation. The legislation function has irrelevant result compare to the number of budget spent for it. The indication can be seen from the fact that DPR do high frequency of'improper'visit to other countries that need great amount of money. Meanwhile, in the function of budgeting, DPR fail to provide transparent budgeting since there were many personal activity of the members who were indicated did corruption and collusion. Moreover,the people's trust to this institution is recently decreasing slightly as this body usually neglect citizen interest in many policy they make. Keywords : house of representative, insignificant resultpermalink: http://ejournal.undip.ac.id/index.php/forum/article/view/3161